2017
DOI: 10.1039/c7nr05883g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast structural evolution and formation of linear carbon chains in single-walled carbon nanotube networks by femtosecond laser irradiation

Abstract: Inter-allotropic structural transformation of sp structured nanocarbon is a topic of fundamental and technological interest in scalable nanomanufacturing. Such modifications usually require extremely high temperature or high-energy irradiation, and are usually a destructive and time-consuming process. Here, we demonstrate a method for engineering a molecular structure of single-walled carbon nanotubes (SWNTs) and their network properties by femtosecond laser irradiation. This method allows effective coalescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Femtosecond (fs) laser with ultrashort pulse durations and high peak power without causing thermal damage to the part is usually employed in nanostructures manufacture and nanomaterials modification [24,25,26,27]. It is an ideal tool for the excitation of surface plasmon resonances (SPRs), because the fs laser excitation can minimize thermal damage in the adjacent nanomaterials and substrate materials [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond (fs) laser with ultrashort pulse durations and high peak power without causing thermal damage to the part is usually employed in nanostructures manufacture and nanomaterials modification [24,25,26,27]. It is an ideal tool for the excitation of surface plasmon resonances (SPRs), because the fs laser excitation can minimize thermal damage in the adjacent nanomaterials and substrate materials [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Arutyunyan et al [28] studied the selective removal of a specific category of SWCNT thin film by resonant ablation through femtosecond pulses. Most recently, the transformation of SWCNT structures into other allotropic carbon structures with effective coalescence through femtosecond laser irradiation was reported by Ha et al [2].…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, the femtosecond laser appeared as a powerful technique to investigate laser matter interactions for micromachining, surface modification, laser surgery, nanostructure generation, structural evolutions, etc. [1,2]. Particularly, femtosecond laser assisted nano-joining has received great attention due to its critical role in the technological development of microelectronics, MEMS, and nano-devices among various applications [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the isolated short linear carbon chains just reached a maximum length of 48 carbon atoms when they were end-capped by some huge functional groups . Therefore, the serendipitous discovery of carbon nanowires (CNWs, LLCCs@CNTs), made of LLCCs inserted inside carbon nanotubes (CNTs) by Zhao et al, paves the way for studying the structure and physical properties, as well as applications, of both LLCCs (carbyne) and CNWs (LLCCs@CNTs). According to the type of CNTs outside LLCCs, CNWs (LLCCs@CNTs) can be categorized into single-walled CNWs (SWCNWs, LLCCs@SWCNTs), double-walled CNWs (DWCNWs, LLCCs@DWCNTs), and muti-walled CNWs (MWCNWs, LLCCs@MWCNTs) . MWCNWs (LLCCs@MWCNTs) and DWCNWs (LLCCs@DWCNTs) were obtained in 2003 and 2011, respectively. ,, Especially in 2016, Shi et al obtained the longest DWCNWs (LLCCs@DWCNTs) in which the LLCCs consisted of >6000 carbon atoms .…”
Section: Introductionmentioning
confidence: 99%